At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To prove by induction that for all positive integers [tex]\( n \)[/tex], [tex]\( 21 \mid \left(4^{n+1} + 5^{2n-1}\right) \)[/tex], we follow these steps:
### Base Case
Let's check the base case when [tex]\( n = 1 \)[/tex]:
[tex]\[ 4^{n+1} + 5^{2n-1} = 4^{1+1} + 5^{2 \cdot 1 - 1} = 4^2 + 5^1 = 16 + 5 = 21 \][/tex]
Since [tex]\( 21 \)[/tex] is divisible by [tex]\( 21 \)[/tex]:
[tex]\[ 21 \mid 21 \][/tex]
The base case holds true.
### Inductive Step
Next, we assume that the proposition is true for some positive integer [tex]\( k \)[/tex]. That is, we assume:
[tex]\[ 21 \mid \left( 4^{k+1} + 5^{2k-1} \right) \][/tex]
This is our induction hypothesis.
We need to prove that the proposition is true for [tex]\( k+1 \)[/tex], i.e., we need to show:
[tex]\[ 21 \mid \left( 4^{(k+1)+1} + 5^{2(k+1)-1} \right) \][/tex]
Simplify the expression:
[tex]\[ 4^{(k+1)+1} + 5^{2(k+1)-1} = 4^{k+2} + 5^{2k+1} \][/tex]
We need to show that [tex]\( 4^{k+2} + 5^{2k+1} \)[/tex] is divisible by [tex]\( 21 \)[/tex].
Express [tex]\( 4^{k+2} \)[/tex] in terms of [tex]\( 4^{k+1} \)[/tex]:
[tex]\[ 4^{k+2} = 4 \cdot 4^{k+1} \][/tex]
Similarly, express [tex]\( 5^{2k+1} \)[/tex] in terms of [tex]\( 5^{2k-1} \)[/tex]:
[tex]\[ 5^{2k+1} = 25 \cdot 5^{2k-1} \][/tex]
Thus, our problem reduces to:
[tex]\[ 4^{k+2} + 5^{2k+1} = 4 \cdot 4^{k+1} + 25 \cdot 5^{2k-1} \][/tex]
Using our induction hypothesis [tex]\( 21 \mid \left( 4^{k+1} + 5^{2k-1} \right) \)[/tex]:
[tex]\[ 4^{k+1} + 5^{2k-1} = 21m \quad \text{for some integer } m \][/tex]
We need to find a way to express [tex]\( 4 \cdot 4^{k+1} + 25 \cdot 5^{2k-1} \)[/tex] in terms of [tex]\( 21 \)[/tex]. Using the fact that:
[tex]\[ 4^{k+1} \equiv -5^{2k-1} \pmod{21} \][/tex]
By substitution [tex]\( 4 \cdot 4^{k+1} \equiv 4 \cdot (-5^{2k-1}) = -4 \cdot 5^{2k-1} \pmod{21} \)[/tex]:
[tex]\[ \Rightarrow 4 \cdot 4^{k+1} \equiv 4 \cdot 4^{k+1} \pmod{21} \][/tex]
Similarly for [tex]\( 25 \cdot 5^{2k-1} \)[/tex]:
[tex]\[ 25 \equiv 4 \pmod{21}, \][/tex]
so
[tex]\[ 25 \cdot 5^{2k-1} \equiv 4 \cdot 5^{2k-1} \pmod{21}. \][/tex]
Combining these results:
[tex]\[ 4 \cdot 4^{k+1} + 25 \cdot 5^{2k-1} \equiv 4 \cdot 4^{k+1} + 4 \cdot 5^{2k-1} \equiv 0 \pmod{21}. \][/tex]
Therefore,
[tex]\[ 21 \mid \left( 4^{(k+1)+1} + 5^{2(k+1)-1} \right) \][/tex]
Thus, by induction, for all positive integers [tex]\( n \)[/tex]:
[tex]\[ 21 \mid \left( 4^{n+1} + 5^{2n-1} \right) \][/tex]
This concludes the proof by mathematical induction.
### Base Case
Let's check the base case when [tex]\( n = 1 \)[/tex]:
[tex]\[ 4^{n+1} + 5^{2n-1} = 4^{1+1} + 5^{2 \cdot 1 - 1} = 4^2 + 5^1 = 16 + 5 = 21 \][/tex]
Since [tex]\( 21 \)[/tex] is divisible by [tex]\( 21 \)[/tex]:
[tex]\[ 21 \mid 21 \][/tex]
The base case holds true.
### Inductive Step
Next, we assume that the proposition is true for some positive integer [tex]\( k \)[/tex]. That is, we assume:
[tex]\[ 21 \mid \left( 4^{k+1} + 5^{2k-1} \right) \][/tex]
This is our induction hypothesis.
We need to prove that the proposition is true for [tex]\( k+1 \)[/tex], i.e., we need to show:
[tex]\[ 21 \mid \left( 4^{(k+1)+1} + 5^{2(k+1)-1} \right) \][/tex]
Simplify the expression:
[tex]\[ 4^{(k+1)+1} + 5^{2(k+1)-1} = 4^{k+2} + 5^{2k+1} \][/tex]
We need to show that [tex]\( 4^{k+2} + 5^{2k+1} \)[/tex] is divisible by [tex]\( 21 \)[/tex].
Express [tex]\( 4^{k+2} \)[/tex] in terms of [tex]\( 4^{k+1} \)[/tex]:
[tex]\[ 4^{k+2} = 4 \cdot 4^{k+1} \][/tex]
Similarly, express [tex]\( 5^{2k+1} \)[/tex] in terms of [tex]\( 5^{2k-1} \)[/tex]:
[tex]\[ 5^{2k+1} = 25 \cdot 5^{2k-1} \][/tex]
Thus, our problem reduces to:
[tex]\[ 4^{k+2} + 5^{2k+1} = 4 \cdot 4^{k+1} + 25 \cdot 5^{2k-1} \][/tex]
Using our induction hypothesis [tex]\( 21 \mid \left( 4^{k+1} + 5^{2k-1} \right) \)[/tex]:
[tex]\[ 4^{k+1} + 5^{2k-1} = 21m \quad \text{for some integer } m \][/tex]
We need to find a way to express [tex]\( 4 \cdot 4^{k+1} + 25 \cdot 5^{2k-1} \)[/tex] in terms of [tex]\( 21 \)[/tex]. Using the fact that:
[tex]\[ 4^{k+1} \equiv -5^{2k-1} \pmod{21} \][/tex]
By substitution [tex]\( 4 \cdot 4^{k+1} \equiv 4 \cdot (-5^{2k-1}) = -4 \cdot 5^{2k-1} \pmod{21} \)[/tex]:
[tex]\[ \Rightarrow 4 \cdot 4^{k+1} \equiv 4 \cdot 4^{k+1} \pmod{21} \][/tex]
Similarly for [tex]\( 25 \cdot 5^{2k-1} \)[/tex]:
[tex]\[ 25 \equiv 4 \pmod{21}, \][/tex]
so
[tex]\[ 25 \cdot 5^{2k-1} \equiv 4 \cdot 5^{2k-1} \pmod{21}. \][/tex]
Combining these results:
[tex]\[ 4 \cdot 4^{k+1} + 25 \cdot 5^{2k-1} \equiv 4 \cdot 4^{k+1} + 4 \cdot 5^{2k-1} \equiv 0 \pmod{21}. \][/tex]
Therefore,
[tex]\[ 21 \mid \left( 4^{(k+1)+1} + 5^{2(k+1)-1} \right) \][/tex]
Thus, by induction, for all positive integers [tex]\( n \)[/tex]:
[tex]\[ 21 \mid \left( 4^{n+1} + 5^{2n-1} \right) \][/tex]
This concludes the proof by mathematical induction.
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.